THE EFFECTS OF ENTREPRENEURIAL SKILLS ON COMPETITIVENESS AT SMEs OF TEMPE CHIPS: THE ROLE OF INNOVATION ABILITY - Pratama, Aldino Reza; Moeljadi, Moeljadi; Rofiq, Ainur (Jurnal Aplikasi Manajemen, 2022)
This study aims to analyze the effect of entrepreneurial skills on competitiveness. This study also analyzes the effect of entrepreneurial skills on innovation ability. This study also analyzes the effect of innovation ability on competitiveness. Finally, this study also analyzes and examines the mediating role of innovation ability on the effect of entrepreneurial skills on competitiveness. The sampling technique in this study used purposive sampling with a sample of 110 SMEs entrepreneurs' tempe chips and data collection using a questionnaire. The data analysis technique used in this study is Partial Least Squares. The study results conclude that entrepreneurial skills positively and significantly affect competitiveness. Entrepreneurial skills have a positive and significant effect on innovation ability. The ability to innovate has a positive and significant impact on competitiveness. Finally, it was found that innovation ability mediates the effect of entrepreneurial skills on competitiveness. Further researchers are advised to add other variables affecting competitiveness, such as entrepreneurial and market orientation.